European idiopathic pulmonary fibrosis Patient Charter: a missed opportunity. Issue 1 (July 2016) - Bonella, Francesco; Wijsenbeek, Marlies; Molina-Molina, Maria; Duck, Annette; Mele, Rosalba; Geissler, Klaus; Wuyts, Wim
We would like to acknowledge the comments of A. Bush and colleagues on the European idiopathic pulmonary fibrosis (IPF) Patient Charter and seize the opportunity to provide additional information on this important initiative. The European IPF Charter paved the way to improve care and raise visibility of the needs of patients affected by ILD http://ow.ly/4nrVHV